One Bright Spot - Haskins, V. author. aut Link
XI, 281 p.
Keywords: For every Aboriginal child taken away by the state governments in Australia, there was at least one white family intimately involved in their life. One Bright Spot is about one of these families - about 'Ming', a Sydney wife and mother who hired Aboriginal domestic servants in the 20s and 30s, and became an activist against the Stolen Generations policy. Her story, reconstructed by her great-granddaughter, tells of a remarkable, yet forgotten, shared history.